Laws stop at borders but guns do not: spillovers from right-to-carry legislation in the United States - Laplana, Antonio de Araujo (2018)
This paper investigates the following research questions: (i) Do changes in Concealed Carry Weapon (CCW) legislation affect crime? (ii) In the case it does affect crime, are there spillover effects on crime rates in neighboring states? We explore state-level changes in gun control legislation in the U.S. from 1986 to 2014, which show a national trend of lowering the requirements for issuing a CCW permit. By employing a differences-in-differences strategy we find that lowering CCW demands raised drug-related crime rates by 15%, on average, in counties within states where the law was changed. Spillover effects in neighboring states also play an important role. In the counties across the state border (but close to it), violent and drug-related crime rates raised, on average, by 13% and 15%, respectively. We also find evidence that such spillover effects are spatial in nature. The results are robust to a variety of tests and are not driven by differential pre-trends.